2018
DOI: 10.15666/aeer/1604_47734788
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nano and Chemical Fertilizers on Physiological Efficiency and Essential Oil Yield of Borago Officinalis L.

Abstract: This study was conducted to compare the effects of nano and chemical fertilizers on physiological efficiency and essential oil yield of Borago officinalis L. during 2013 and 2014 crop years. The different levels of fertilizers were used as main factors in 11 levels including iron-sulphate and nanoiron, zinc and nano-zinc, urea and nano-urea, potassium sulphate and nano-potassium, micro-complete and micro-complete nanosuper and control. The application methods of fertilizers were considered as secondary factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 16 publications
3
8
0
Order By: Relevance
“…6a-c). The current results agreed with the previous results 15,21,27,29,31,33,36 Leaves to shoot ratio didnʼt show significant differences due to the use of either seaweed extract or NPK fertilizer in comparison to the control treatment (Fig. 7a).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…6a-c). The current results agreed with the previous results 15,21,27,29,31,33,36 Leaves to shoot ratio didnʼt show significant differences due to the use of either seaweed extract or NPK fertilizer in comparison to the control treatment (Fig. 7a).…”
Section: Resultssupporting
confidence: 93%
“…Additionally, nitrogen and magnesium elements can be released by chemical fertilizers and incorporated into the chlorophyll moleculeʼs porphyrin ring. Potassium enhances nitrogenʼs influence on photosynthesis through an oligodynamic role or participation in the energy transformation, activating kinases and osmotic absorption 27 . Current results agreed with other results 26,[28][29][30][31] .…”
Section: Resultsmentioning
confidence: 99%
“…The increase in the vegetative weight may be attributed to the increase in the plant height and leaves number of treated plants. These results are in agreement with (Mahmoodi et al, 2018) on Borago officinalis L. and (Salama, 2012) on Phaseolus vulgaris L. and Zea mays L. indicated Nano-fertilizers increase availability of nutrient to the growing plant which increase chlorophyll formation, photosynthesis rate, dry matter production and result improve overall growth of the plant. Moreover, (El-Sayed, 2014) on Schefflera arboricola found that the application of GA 3 increased the fresh and dry weight of stems.…”
Section: Fresh and Dry Weight Of Leaves/plant (G)supporting
confidence: 87%
“…In this connection, (Singh, 2017b) reported that Nano-fertilizer enhance leaf area index, number of leaves/plant, dry matter production and rate of the photosynthesis which result more production and translocation of photosynthets to different parts of the plant. Similar results were reported by (Jameel and Al-Tai, 2018) on sweet fennel, cumin and anise and (Mahmoodi et al, 2018) on Borago officinalis L. As well as, (El-Khateeb et al, 2010) on Calia Secundiflora found that GA 3 gave marked increases in the fresh and dry weights of leaves, it can be attributed to the increase both plant height and number of leaves plant. Tables (3 and 4) revealed that the application of different ratios of Nano-fertilizer and GA 3 increased the fresh and dry weight of stems for Croton plants when compared with control.…”
Section: Fresh and Dry Weight Of Leaves/plant (G)supporting
confidence: 81%
“…The current unfavourable food situation in the world due to the lack of food for many countries requires the leading producers of agricultural products, which includes Russia, to increase the production of food, especially from plant-growing raw materials, as much as possible, despite the negative projected global warming and critical droughts recurring from year to year in many regions and in particular in the Russian Federation [1][2][3]. In solving this problem, it is necessary to further expand the planting of highly productive crops, which include corn [4][5][6], improve its cultivation technologies using innovative technical and technological products, in particular the use of nitrogen fertilisers [7][8][9][10] preferably in liquid form [1,4,8] based on a carbamide-ammonia mixture -CAM (CAM-32, CAM+S). CAM is a unique highly effective liquid fertiliser with a prolonged effect due to the versatile effect of three forms of nitrogen on plants: nitrate, ammonium and amide ones, and only the amide form can be absorbed by the vegetative part of agricultural plants [1,6].…”
Section: Introductionmentioning
confidence: 99%